Creating respectful workplaces for nurses in regional acute care settings: A quasi‐experimental design. Issue 1 (23rd June 2022) - Hawkins, Natasha; Jeong, Sarah Yeun‐Sim; Smith, Tony; Sim, Jenny; Clapham, Matthew
Abstract: Aim: To examine self‐reported exposure and experiences of negative workplace behaviour and ways of coping of nursing staff before and after educational workshops. Design: A Quasi‐experimental design. Method/Setting/Participants: Data were collected pre‐ /postworkshops using a structured questionnaire. Nurses ( N = 230) from 12 units in four regional acute care hospitals were invited to complete a pre‐intervention survey. Educational workshops were then implemented by the organization at two of the hospitals, after which, follow‐up surveys were undertaken. Results: There were 74 responses in the pre‐intervention and 56 responses in the postintervention time period. There were 111 participants who attended the educational intervention, 20% ( n = 22) completed the follow‐up survey. Participants were more likely exposed to work‐related bullying acts and they used problem‐focused coping strategies and sought social support as a way of coping when exposed to the negative behaviours. Overall, there was a decrease in both bullying and incivility experienced by participants; however, our findings were unable to establish that a statistically significant difference was made due to the implementation of the intervention. Study Registration: Australian New Zealand Clinical Trials Registry (Registration No. ACTRN12618002007213; December 14, 2018).